'Dash me with Amorous Wet, I can Repay You'. (21st October 2022) - Murray, Caleb
Abstract : Walt Whitman's poetry is famously full of 'self' and self-contradicting: 'Do I contradict myself? / Very well then I contradict myself, / (I am large, I contain multitudes.)' The scholarly attention to paradox and contradiction often takes the form of an attention to various 'binaries' in Whitman's prose and poetry; well-trod binaries include body-soul, sacred-profane, nature-culture, and woman-man. However, a queer attention to the poetic construction of such binaries reveals them to be fluid and ultimately non-binary. Whitman and his speakers construct binaries that relate to religion, gender, and nature, but in poeticizing the construction of binary logic (e.g., man-woman), Whitman and his speakers reveal such purportedly self-contained and discrete domains to be open, fluid, and co-constituting. Recognizing the poetic performance of 'binary' logic will reshape reader's understanding of ethical and political implications of Whitman's queerly relational nature ethics.